2023
DOI: 10.3389/fpsyg.2023.1040214
|View full text |Cite
|
Sign up to set email alerts
|

School climate and left-behind children’s achievement motivation: The mediating role of learning adaptability and the moderating role of teacher support

Abstract: School climate has been reported to have an important impact on children’s achievement motivation, but the mechanism for the impact of school climate on left-behind children has not been fully explored. The purpose of this study is to investigate the roles of left-behind children’s learning adaptability and teacher support in mediating and moderating the relationship between school climate and achievement motivation. In this study, 1,417 left-behind children were surveyed. The results showed that: (1) after co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Furthermore, the variance inflation factor (VIF) was used to establish the occurrence of multicollinearity amongst variables (Yang et al, 2012). The findings reveal that the VIF values ranged from 1.30 to 1.81, significantly less than the critical value of 10, while tolerance values ranged from 0.55 to 0.72, which were greater than 0.1 (Zhao et al, 2023) Therefore, there was no multicollinearity problem in the mode.…”
Section: Common Methods Bias Test Multicollinearity Diagnosis and Cor...mentioning
confidence: 81%
“…Furthermore, the variance inflation factor (VIF) was used to establish the occurrence of multicollinearity amongst variables (Yang et al, 2012). The findings reveal that the VIF values ranged from 1.30 to 1.81, significantly less than the critical value of 10, while tolerance values ranged from 0.55 to 0.72, which were greater than 0.1 (Zhao et al, 2023) Therefore, there was no multicollinearity problem in the mode.…”
Section: Common Methods Bias Test Multicollinearity Diagnosis and Cor...mentioning
confidence: 81%
“…School climate refers to the quality and characteristics of school life, encompassing teacher support, peer support, and opportunities for autonomy, emphasizing the interpersonal relationships among students and between students and teachers [41]. A positive school climate signi cantly promotes the psychological and behavioral development of left-behind children [42], providing them with a sense of security and emotional support, thus reducing the occurrence of adverse emotions [43]. Studies have found a signi cant negative correlation between school climate and adolescent depression; adolescents who perceive a school climate as negative are more prone to experiencing depressive issues [44][45][46].…”
Section: The Moderating Role Of School Climatementioning
confidence: 99%
“…In China, a growing number of studies started looking at the resilience research of LBC and shared similar findings: Family poverty contributes to the resilience of LBC and their learning attitudes. They hope to get away from their present predicament and change their lives by improving their educational achievements (Dai & Peng, 2021; Wu et al., 2014; Zhao et al., 2023).…”
Section: Literature Reviewmentioning
confidence: 99%